Experimental Investigation of Snow Accumulations on Two-Span Single-Pitched Roofs Based on a New Similarity Criterion - Zhang, Guolong; Zhang, Qingwen; Mo, Huamei; Li, Rui; Liu, Mengmeng; Fan, Feng (Frontiers in Earth Science, 2022)
Uneven snow distribution plays a main role in the collapse of two-span single-pitched roofs because of the intensified snow accumulation in the valleys and eaves. The roof pitches, wind velocities, and wind directions are the main reasons that cause unbalanced snowdrifts as they drastically affect the flow fields around the roofs. This research investigates the snow distribution characteristics on two-span single-pitched roofs based on the snow-wind combined experiment facility and new similarity criteria. Firstly, the setup of the experiment facility is introduced, and the wind fans matrix and snowfall simulator are calibrated, respectively. Then, a new Froude number similarity, based on the modification of friction velocity ratio, is proposed, and its reliability as a criterion is verified. Finally, experiments on two-span single-pitched roofs are conducted using the new similarity criteria to study the snowdrifts patterns under different conditions. The mechanism of snow accumulations on roofs is explained with the help of CFD calculation. The results show that the valley and eave on the second windward roof bear a larger snow load.